Semen Cassiae Extract Improves Glucose Metabolism by Promoting GlUT4 Translocation in the Skeletal Muscle of Diabetic Rats - Zhang, Meiling; Li, Xin; Liang, Hangfei; Cai, Huqiang; Hu, Xueling; Bian, Yu; Dong, Lei; Ding, Lili; Wang, Libo; Yu, Bo; Zhang, Yan; Zhang, Yao (Frontiers in Pharmacology, 2018)
Diabetes mellitus is a clinical syndrome characterised by hyperglycaemia; its complications lead to disability and even death. Semen Cassiae is a traditional Chinese medicine, which has anti-hypertensive, anti-hyperlipidaemia, anti-oxidation, and anti-ageing properties. Our study was designed to evaluate the action of total anthraquinones of Semen Cassiae extract (SCE) on the improvement of glucose metabolism in diabetic rats and to elucidate the underlying mechanism. First, we evaluated the effect of SCE on normal rats. Next, we observed the effect of SCE using a rat model of diabetes, which was established by feeding rats with high-energy diet for four weeks and a single intraperitoneal injection of streptozotocin (30 mg/kg) three weeks after starting the high-energy diet. Rats in different SCE groups (administered 54, 108, and 324 mg/kg/day of SCE) and metformin group (162 mg/kg/day, positive control drug) were treated with the corresponding drugs one week before starting high-energy diet and treatment continued for five weeks; meanwhile, rats in the control group were administered the same volume of sodium carboxymethyl cellulose solution (vehicle solution). One week after streptozotocin injection, fasting blood glucose, oral glucose tolerance, fasting serum insulin, and serum lipids were quantified. Finally, the expression of proteins in the PI3K-Akt-AS160-GLUT4 signalling pathway was detected by western blotting. The data indicated that the levels of fasting blood glucose and serum lipids were significantly lowered, and oral glucose tolerance and fasting serum insulin were markedly increased in diabetic rats treated with SCE (108 mg/kg/day); however, SCE did not cause hypoglycaemia in normal rats. The molecular mechanisms were explored in the skeletal muscle. SCE markedly restored the decreased translocation of GLUT4 in diabetic rats. Moreover, the protein expression of phosphorylated-AS160 (Thr642), phosphorylated-Akt (Ser473), and PI3K were significantly increased after SCE treatment in the skeletal muscle. These results indicate that SCE exerts an anti-hyperglycaemic effect by promoting GLUT4 translocation through the activation of the PI3K-Akt-AS160 signalling pathway. Our findings suggest that treatment with SCE, containing anthraquinones, could be an effective approach to enhance diabetes therapy.